Medical Bondage Race, Gender, and the Origins of American Gynecology - Owens, Deirdre Cooper (University of Georgia Press, 2017)
Medical Bondage explores how, in the nineteenth century, experimental surgeries on enslaved and laboring women enabled the rise of American gynecology as a medical specialty, and shaped our understanding of race. Merging women's, medical, and social history, the book makes Black and Irish women's lives-not just their bodies-part of an origins story of American medicine (one that has largely been told with an exclusive focus on white male historical actors).